SISTEM REKOMENDASI PEMBERIAN SUBSIDI LPG 3KG TERHADAP MASYARAKAT MENGGUNAKAN DECISION TREE C4.5 - As’arie, Mohammad Hasan; Razaq, Jeffri Alfa (Proceeding SENDI_U, 2020)
LPG 3Kg is now an important necessity for many people. LPG 3 kg is an item that is subsidized by thegovernment for the community, although labeled 3kg LPG cylinder is listed for the poor not a few people whoearn enough to still use these subsidized goods, for that PT.Muara Putra Perdana's agent appealed andeducated the base so that distribute LPG LPG on target with various cases of consumer conditions as to beentitled to get subsidized LPG.The purpose of this study is to determine the granting of subsidy rights to 3kg LPG base consumers ontarget based on the attributes that play a role by applying the appropriate algorithm. The algorithm used in thisstudy is Decision Tree C4.5. Researchers chose this algorithm because the C4.5 algorithm is easy to understandand produces a simple decision tree and has an analysis with high accuracy and appropriate recommendationsbased on parameters of the specified attributes.